Neoliberal nationalism : immigration and the rise of the populist right - Joppke, Christian (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2021)
"The Brexit and Trump "double shock" of 2016 marks a deep caesura in the history of liberal societies. In the center of the populist storm is immigration. It is no longer sufficient, if it ever was, to look at Western states' immigration and citizenship policies through the singular lens of advancing liberalism. Instead, two additional forces have to be factored-in: a new nationalism, but also the neoliberal restructuring of governing and society in which this nationalism is generated. Through a comparative look at changing immigration and citizenship policies across the Western state world, Christian Joppke demonstrates that many of the new restrictions can actually be accounted for within a neoliberal rather than a nationalist framework. Moreover, some of the restrictive changes, such as the rise of "earned citizenship", are due to neoliberalism and nationalism working in tandem, in terms of a genuinely neoliberal nationalism. The neoliberalism-nationalism nexus is complex, its components sometimes opposing but sometimes complementing or even constituting one another. The nexus is still unlikely to reverse nondiscriminatory immigration and citizenship policies whose liberal basis remains intact"--
The neoliberalism-nationalism nexus -- Courting the top, fending-off the bottom: immigration in the populist storm -- More difficult to get, easier to lose, less in value: the rise of earned citizenship -- The end of liberalism?
Includes bibliographical references (pages 284-316) and index.
Keywords: Neoliberalism -- Western countries; Nationalism -- Western countries; Populism -- Western countries; Right and left (Political science) -- Western countries; Western countries -- Emigration and immigration -- Social aspects; Western countries